Examination of the causes of mortality in non-beak-trimmed pure line laying hens with special regard to aggression - Zomborszky, Zoltán; Milisits, Gábor; Budai, Zoltán; Szász, Sándor; Pőcze, Olga; Ujvári, Jolán; Farkas, Péter Tamás; Garamvölgyi, Erik; Horn, Péter; Sütő, Zoltán (Acta Agraria Kaposváriensis, 2020)
The experiment was started with 1,508 Rhode Island Red (RIR) and 1,820 Rhode Island White (RIW) type non-beak-trimmed day-old pullets, which were originated from 58 RIR and 70 RIW different pedigree cocks, respectively. From all of the 128 cocks 26 half sibling offspring were tested. The pure line pullets were raised up to 18 weeks of age in a closed building, in deep litter pens and moved to the laying house and placed into three types of keeping systems [furnished cage, alternative pen (litter and floor) and conventional cage] thereafter. The number of dead birds and the cause of mortality were recorded daily during the whole rearing and egg-laying period, up to 72 weeks of age. During the rearing period the most frequent cause of mortality was wasting, which accounted for nearly 36% of the total mortality. Aggression was responsible for 28.3% of the total mortality. Depending on the type of the pullets (RIR or RIW), differences were observed in the frequency of occurrence of mortality causes. For example, oedema and beak deformation occurred only in the RIR, whereas technological injury and aggression only in the RIW pullets during the rearing period. During the egg-laying period aggression was the most common cause of mortality. Its lowest occurrence was observed in the alternative pens. In both of the examined types there were found cocks, whose offspring died exclusively by aggression, and cocks, whose offspring did not show any loss due to aggression. The ratio of these cocks differed significantly (P
Keywords: pullet; laying hen; feather pecking; aggression; cannibalism